Potential Rhizospheric Bacteria of Local Rice Rice “Cempo Laut” in Merauke - Nurhening Yuni Ekowati; Rosmala Widijastuti (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2023)
Non-cultivated local rice is known to have high resistance to various environmental stresses. This resistance is inseparable from the role of symbiotic and non-symbiotic rhizosphere bacteria that live in the root rhizosphere. This study aims to isolate and study the potential of rhizobacteria that live around the roots of non-cultivated local rice plants. This research is exploratory research to obtain rhizobacterial isolates that can stimulate plant growth and development and can be applied to cultivated rice plants. Soil samples were taken from Mimi Baru Village, Jagebob District. Sampling was carried out aseptically. Isolation was carried out using the multilevel dilution method. Isolates grown in NA media were then subcultured to obtain pure isolates. The isolates obtained were then characterized morphologically according to Bergey's Manual of Determinative Bacteriology and characterized microscopically. Based on the results of this study it can be concluded that there were 12 bacterial isolates in the local rice